Microbial Source Tracking of Fecal Indicating Bacteria in Coral Reef Waters, Recreational Waters, and Groundwater of Saipan by Real-Time Quantitative PCR - Sinigalliano, Christopher; Kim, Kiho; Gidley, Maribeth; Yuknavage, Kathy; Knee, Karen; Palacios, Dean; Bautista, Charito; Bonacolta, Anthony; Lee, Hyo Won; Maurin, Larry (Frontiers in Microbiology, 2021)
The Commonwealth of the Northern Mariana Islands (CNMI) recently identified the need to improve its capacity for detecting and tracking land-based sources of pollution (LBSP) in coastal waters, particularly microbial contaminants like fecal indicator bacteria (FIB). Reported here is a baseline study of a suite of host-specific FIB microbial source tracking (MST) markers in the coastal shoreline and reef waters around the island of Saipan. Three sampling campaigns were conducted in September 2017, March 2018, and August 2018. Samples were collected from the nearshore surface waters of Saipan, the reef waters of Saipan Lagoon, and groundwater from beaches along the Saipan Lagoon shoreline. Measurements of submarine groundwater discharge (SGD) into nearshore waters and isotopic source tracking of nitrogen inputs were conducted concurrently with MST. Environmental DNA was extracted from the samples and analyzed by quantitative polymerase chain reaction (qPCR) for MST gene markers of fecal Bacteroidales specifically associated with humans, dogs, cows, and pigs, and for an MST gene marker of Catellicoccus associated with seabirds. MST assessments were combined with local knowledge, assessments of sanitary infrastructure, and routine watershed surveys. This study identified hotspots of human FIB along the western Saipan Lagoon shoreline in both surface waters and groundwater, plus another hotspot of human FIB at a popular tourist bathing area known as the Grotto. FIB hotspots on the Lagoon shoreline coincided with areas of high SGD and nitrogen isotopic data indicating sewage-derived N inputs. It appears that faulty sanitary infrastructure may be contributing to inputs to Saipan Lagoon, while bather shedding is likely a primary input for the Grotto area. Moderate levels of dog fecal contamination were common and widespread across the island. High levels of seabird fecal contamination were more random, both spatially and temporally, and mostly concentrated along the less developed northeast region of Saipan. No significant levels of cow or pig fecal marker were detected in coastal water samples. This study provides demonstration and establishment of analytical capacity to resource management in CNMI for MST technology to aid in trouble-shooting water quality issues involving land-based sources of microbial contaminants to CNMI coastal waters.